Social services for newcomers to Canada: A systematic review of the evidence on provision, management, and outcomes of available services - Sharma, Aru (My University, 2016)
Background: Canada brings in more than 200 000 newcomers annually, many of who require the use of social services to aid in their integration process. In 2011, the federal government made a 12% cut to the budget allocated for newcomer services, resulting in the closure of many services and decreased overall service capacity. The purpose of this study is to understand how social services for newcomers are provided, managed, evaluated, and funded. Methodology: Seven electronic databases (CINAHL, Global Health, Medline, Ovid Healthstar, PAIS, PsycINFO, and Sociological Abstracts) were searched using search terms related to newcomers, social services, and Canada (as a jurisdictional limit). Thematic Synthesis methodology was used to code textual data, and extract descriptive themes to further analyze to determine analytical themes. Results: A total of 20 studies were selected for the systematic review (19 through database search, 1 through a search of references). From these, 7 descriptive themes were found and analyzed to determine 2 analytical themes. Findings exhibit unique interactions between different levels of service delivery for newcomers, but also demonstrate scarcity of data and research dedicated to the topic. Conclusion: Due to significant changes in the governance structures that determine what services are provided and how they are funded, it is essential that future research focus on these changes and their impact on newcomer integration. Additionally, a deeper understanding of the relationships between and within different levels of service delivery is required.
Keywords: social services; newcomers; Canada; immigrant; refugee; settlement; integration